2019
DOI: 10.1080/10826084.2019.1577457
|View full text |Cite
|
Sign up to set email alerts
|

An international study of analgesic dependence among people with pain in the general population

Abstract: Background: Overuse of and dependence on analgesics (including opioids and other pain medications) are major international public health problems. Objective: To identify influences on analgesic dependence among analgesic users in the general populations of different countries. Methods: Online surveys of 1,283 people with pain in the UK, USA, Australia, Germany, Egypt and China/Macau/Hong Kong. Results: Levels of analgesic overuse and dependence were highest in Egypt and lowest in China/Macau/Hong Kong. In ever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…However, it remains possible that quality of life among women with menstrual pain could be increased by improved analgesic pain management, provided this can be achieved without risking analgesic dependence. 35 Two limitations of the study are that the sample size was not large and all the data were selfreported, with no objective clinical data. Future research might explore the role of pain acceptance among larger samples of women with dysmenorrhea in the general population, or clinical samples of women seeking or receiving medical help for dysmenorrhea, including clinical measures.…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains possible that quality of life among women with menstrual pain could be increased by improved analgesic pain management, provided this can be achieved without risking analgesic dependence. 35 Two limitations of the study are that the sample size was not large and all the data were selfreported, with no objective clinical data. Future research might explore the role of pain acceptance among larger samples of women with dysmenorrhea in the general population, or clinical samples of women seeking or receiving medical help for dysmenorrhea, including clinical measures.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in another study, no statistically significant difference was found in terms of HCAM-related attitudes between pregnant women who used herbal medicine and those who did not use herbal medicine [ 39 ]. In a web-based study, where the participants were from the UK, the US, Australia, Germany, Egypt, and China, while the Chinese participants were found to have positive attitudes towards HCAM (26.36±6.00), the Egyptian participants were determined to have negative attitudes (37.02±3.92) [ 40 ]. It was reported in e previous study that half of the pregnant women had a positive attitudes towards HCAM [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Being an unstable compound, ozone stimulates the production of oxidizing free radicals which selectively damage the cell wall and plasma membrane of microorganisms by hampering their enzymatic metabolism, thereby acting as a potent antimicrobial agent [1,11,18,19,20,21]. The anti-inflammatory action of ozone is attributed to its ability to promote the production of biologically active compounds such as leukotrienes, prostaglandins, and interleukins, which are known for their anti-inflammatory and analgesic actions.…”
Section: Discussionmentioning
confidence: 99%